2020
DOI: 10.1158/1078-0432.ccr-19-3239
|View full text |Cite
|
Sign up to set email alerts
|

Phase I Study of TAK-659, an Investigational, Dual SYK/FLT3 Inhibitor, in Patients with B-Cell Lymphoma

Abstract: are employed by Millennium Pharmaceuticals Inc., a wholly owned subsidiary of Takeda Pharmaceutical Company Limited. S. Wang has ownership interests in Takeda Pharmaceutical Company Limited. K. Stumpo has equity ownership in Astra Zeneca and Teva, and has family members with stock ownership in Bristol-Myers Squibb, AstraZeneca, GSK. I. Proscurshim is a former employee of Agenus. F. Bosch declares consultancy for, and has received honoraria and paid expert testimony from Roche, Novartis, Janssen, AbbVie, Gilead… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(43 citation statements)
references
References 38 publications
4
39
0
Order By: Relevance
“…If SYK inhibitors in the future could also enter this pharmacological armamentarium for AML remains an unanswered question. However, our data supported an effect of SYK inhibition particularly in FLT3 mutated cases, and special TAK-659, which has inhibitory effects against both FLT3 and SYK, seems promising for use in hematological malignancies [ 18 ]. The approaches of dual SYK and FLT3 inhibition was further supported by preclinical data, indicating that SYK is a critical regulator of FLT3 in AML [ 9 ].…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…If SYK inhibitors in the future could also enter this pharmacological armamentarium for AML remains an unanswered question. However, our data supported an effect of SYK inhibition particularly in FLT3 mutated cases, and special TAK-659, which has inhibitory effects against both FLT3 and SYK, seems promising for use in hematological malignancies [ 18 ]. The approaches of dual SYK and FLT3 inhibition was further supported by preclinical data, indicating that SYK is a critical regulator of FLT3 in AML [ 9 ].…”
Section: Discussionsupporting
confidence: 56%
“…Several SYK inhibitors have recently been developed, and bioavailable SYK inhibitors have entered clinical trials for patients with AML [ 17 , 18 , 19 ], with promising results [ 17 , 18 , 19 , 20 , 21 ]. Previous in vitro studies in mouse models have resulted in the impaired growth of AML cells [ 2 , 10 ]; however, the underlying molecular events of SYK signaling have not been investigated in a large context [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The mTORi temsirolimus was approved in 2009 in Europe for R/R MCL based on its efficacy in two phase 2 studies, showing ORR of 38%-41% in monotherapy [122,123], later confirmed in phase 3 studies, with ORR between 22%-47% [124,127]. Regarding SYKi, fostamatinib showed modest activity in monotherapy in both MCL and DLBCL in a phase 1/2 study, with ORR of 11% and 22% respectively [135] and, more recently, TAK-659, a dual inhibitor of SYK and FMS-like tyrosine kinase 3 (FLT3), showed ORR of 28% in patients with R/R DLBCL [136]. Studies evaluating these and other inhibitors of mTOR and SYK, both in monotherapy and in combination, are summarized in Table 1.…”
Section: Clinical Experience With the Targeting Of Apical Bcr Kinases In Dlbcl And MCLmentioning
confidence: 97%
“…The mTORi temsirolimus was approved in 2009 in Europe for R/R MCL based on its efficacy in two phase 2 studies, showing ORR of 38-41% in monotherapy [ 121 , 122 ], later confirmed in phase 3 studies, with ORR between 22-47% [ 123 , 126 ]. Regarding SYKi, fostamatinib showed modest activity in monotherapy in both MCL and DLBCL in a phase 1/2 study, with ORR of 11% and 22%, respectively [ 148 ], and, more recently, TAK-659, a dual inhibitor of SYK and FMS-like tyrosine kinase 3 (FLT3), showed ORR of 28% in patients with R/R DLBCL [ 152 ]. Studies evaluating these and other inhibitors of mTOR and SYK, both in monotherapy and in combination, are summarized in Table 1 and Table 2 .…”
Section: Pharmacological Targeting Of Bcr Upstream Kinases and Its Li...mentioning
confidence: 99%